The market reaction to disclosures related to goodwill after SFAS No. 142. - Shough, Evan Martin. (My University, 2005)
Abstract not available.
Keywords: Business Administration, Accounting.; Goodwill (Commerce) Accounting Standards United States.; Intangible property Accounting Standards United States.; Goodwill and other intangible assts (Financial Accounting Standards Board)